Contribution of ticagrelor therapy in patients with acute coronary syndrome and patients with myocardial infarction to the achievement of State Program "Health Development" target in Russia as a whole and Russian regions in 2023-2025 - M. V. Zhuravleva; S. K. Zyryanov; F. N. Paleev; A. N. Yakovlev; Yu. V. Gagarina; T. V. Marin (Российский кардиологический журнал, 2024)
Aim. To evaluate the contribution ticagrelor compared with clopidogrel therapy in patients with acute coronary syndrome (ACS) and patients with myocardial infarction (MI) to achieving the State Program "Health Development" target "decrease of cardiovascular mortality" in the country as a whole and Russian regions in 2023-2025.Material and methods. In the first year of therapy, all patients over 18 years of age with a confirmed diagnosis of ACS who were indicated for dual antiplatelet therapy (DAPT) were considered as the target population. In the second and third years, therapy was continued by patients at high risk of coronary events after MI. The number of deaths that could be additionally prevented within 1 year after diagnosis using DAPT with ticagrelor compared with DAPT with clopidogrel was calculated based on the PLATO trial. For post-MI patients, the number of deaths that could be prevented in the second and third years of therapy using DAPT with ticagrelor+acetylsalicylic acid (ASA) compared with ASA monotherapy was calculated based on the PEGASUS trial. The proportion of the target "decrease of cardiovascular mortality of the population" in 2023-2025 that can be achieved by using DAPT with ticagrelor instead of clopidogrel or ASA monotherapy was calculated.Results. The use of ticagrelor as part of DAPT for patients with ACS will make it possible (compared to DAPT with clopidogrel or ASA) to contribute to achieving "decrease of cardiovascular mortality" target in the Russian Federation:in 2023 — 8,0% due to expected prevention of 4443 cardiovascular deaths,in 2024 — 30,3% due to expected prevention of 4753 cardiovascular deaths,in 2025, 5366 cardiovascular deaths can be Conclusion. The use of ticagrelor as part of DAPT for patients with ACS will contribute to achieving "decrease of cardiovascular mortality" target in the Russian Federation.